براہوئی افسانہ:روایت و راجی سرحال: The social and traditional topics of Brahui short story - Nazir, Iqbal; Sabir, Abdul Razzaq; Baloch, Manzoor (Al-Burz, 2016)
The foundation of the Brahui short stories was laid in 1955 and its very first short story was "Musafir" which was written by the first Brahui short story writer Haibat Khan. After this, there were a lot of the new writers and though it was a bit slow, but the writers kept writing. Generally, the new writers brought up the topics like tribal customs and social behaviors which is still continued with minor modifications. We cannot say that these sorts of topics can’t be the topics of fiction and especially short stories. Obviously these are burning social issues which are seen in the Brahui short stories and these issues must be brought forward but the need of new style of writing is after all the requirements of Brahui short stories because the common and similar topics reduce the colorful circle of the short stories and as a result it loses its readers. Further, Brahui short story needs a lot of practice to improve its technique. Beside this, as per today’s literary requirements, historical, economical and psychological aspects are also to be brought forward in order to enhance the topics of Brahui short story.